GEOLOGI TEKNIK JATINANGOR: STUDI DAYADUKUNG TANAH BERDASARKAN PREDIKSI KADAR AIRTANAH UNTUK MENUNJANG ECO-CAMPUSS DI JATINANGOR - Sophian, Irvan; Zakaria, Zufialdi; Prianda, Yogi; Utomo, Rizky Narendra (Bulletin of Scientific Contribution, 2014)
Research location at Rector Building area, Unpad Campus, Jatinangor. The study is a part of research of Jatinangor engineering geology. Strength prediction of soil bearing capacity for shallow foundation is performed by measuring the water content of the soil at four locations sampled. Based on the formula of Hirnawan & Zakaria (1991), a variable value of unit weight (γ)  = 1.73 T/M3; cohesion (c ) = 7.80 T/M2; and angle of friction= 13.69 degrees. The soil variables based on the value of water content by 43.85%. The result of soil bearing capacity (in dry conditions) around the ground surface of the rector building area is as follows: Type of foundations Square = 17,732 T/M2; Circular foundation type = 17,708 T/M2; Continuous foundation type = 13.714 T/M2. In wet conditions, the value of carrying capacity must be calculated again.